(untitled) (Journal of the Bangladesh Agricultural University, 2018)
Tanguar haor wetland is one of the listed Ramsar sites enrich with biodiversity variety and provides several ecosystem services with significant contribution to the national economy of Bangladesh. But these services were decreasing day by day due to natural and anthropogenic activities. The purposes of this study were to identify the utilized ecosystem services by communities, economic values of utilized ecosystem services and the basic reasons for depleting of ecosystem services. Data were collected through baseline survey, checklists, face to face questionnaire survey and focus group discussion (FGD) from 120 residential respondents and 50 tourist respondents by accepting random sampling techniques during November, 2016 to September, 2017. Physiochemical characteristics of the water were determined where the mean temperature and pH were 28.26°C and 7.72 respectively. The highest TDS, EC, DO, NO3 and PO4 values were 1020 (mg L−1), 1460 (μS cm−1), 8.56 (mg L−1), 1.769 (mg L−1) and 0.078 (mg L−1), respectively. Commonly utilized ecosystem services were crops, vegetables, fuel, fresh water, fishes and migratory birds, climate regulation, water purification, natural hazards protection, aesthetic, social relations, recreation & tourism, health benefit, primary production, nutrient cycling, water cycling habitats for species and provision of habitat etc. Market Value Method (MVM) and Contingent Value Method (CVM) were applied to measure the economic value of Tanguar haor wetland services. DPSIR framework and Impact Matrix (IM) were applied for conceptual analysis to identify the effects on ecosystem services. Total economic value of 39 ecosystem services of Tanguar haor was estimated at 174039980 BDT year−1. Mismanagement of biodiversity, over exploitation, sedimentation of haor, climate change, illegal hunting, land use changes and habitat changes were the responsible factors for depleting ecosystem services. The impact factor (4.161) was identified by natural and anthropogenic factors on ecosystem services. There have a vast prospect of the Tanguar haor wetland services for near communities. Finally the research suggested several sustainable management approaches which have the potentiality to protect the services of the wetland. J. Bangladesh Agril. Univ. 16(2): 237-243, August 2018